(untitled) (Bangladesh Journal of Botany, 2019)
The chemical composition of the essential oil of Photinia serrulata L. flowers obtained by hydrodistillation was analyzed by GC/MS for the first time. The major compounds of the oil were found to be benzoic aldehyde (75.2%), docosane (4.0%), phenethyl alcohol (3.0%), pentacosane (1.3%) and benzyl alcohol (1.2%).